Performance-based seismic design of self-centering steel frames with SMA-based braces. (1st January 2017) - Qiu, Can-Xing; Zhu, Songye
Highlights: Investigated seismic performance of SMA-based braced frames (SMABs). Proposed a performance-based seismic design (PBSD) for seismic-resisting self-centering SMABFs. Considered hysteretic parameters and high-mode effect in the PBSD for SMABFs. Abstract: This study proposes a performance-based seismic design (PBSD) method for steel braced frames with novel self-centering (SC) braces that utilize shape memory alloys (SMA) as a kernel component. Superelastic SMA cables can completely recover deformation upon unloading, dissipate energy without residual deformation, and provide SC capability to the frames. The presented PBSD method is essentially a modified version of the performance-based plastic design with extra consideration of some special features of SMA-based braced frames (SMABFs). Four six-story concentrically braced frames with SMA-based braces (SMABs) are designed as examples to illustrate the efficacy of the proposed design method. In particular, the variability in the hysteretic parameters of SMAs, such as the phase-transformation stiffness ratio and the energy dissipation factor, is considered in the PBSD method. Accordingly, four SMABFs are designed with different combinations of these hysteretic parameters. The seismic performance of the designed frames is examined at various seismic intensity levels. Results of nonlinear time-history analyses indicate that the four SMABFs can successfully achieve the prescribed performance objectives at three seismic hazard levels. The comparisons among the designed frames reveal that the SMABs with greater hysteretic parameters result in a more economical design in terms of the consumption of steel and SMA materials.